Infrastructural Critique. The Upside-Down of the Bottom-Up: A Case Study on the IBA Berlin 84/87 - Eva Maria Hierzer; Philipp Markus Schörkhuber (Footprint)
Participation in planning is a logical consequence of the democratisation of society due to the social and cultural changes related to modernism. Anarchistic participation, as in Autogestion, within a development process, is a critical utopian alternative draft to existing power structures. The participatory turn represented by the International Building Exhibition Berlin 1987 (IBA) meant the institutionalisation of these utopian ideas, resulting in a heterotopian notion of participation instrumentalised by governing and economic forces.